Proceedings of the Fifth IEEE International Symposium on Signal Processing and Information Technology, 2005.
DOI: 10.1109/isspit.2005.1577145
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic signatures of WLAN cards and network security

Abstract: The proliferation of wireless devices and the availability of new wireless applications and services raise new privacy and security concerns. Although network-layer anonymity protects the identities of the communication endpoints, the physical layer of many wireless communication protocols offers no such guarantee. The electromagnetic signal transmitted over an open communication medium can be monitored, captured, and analyzed in an effort to trace and identify users of wireless devices. In this paper we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…Perhaps the most intuitive and straightforward way of radiometric analysis was studied by Remley [29], who visually identified differences between signals of different 802.11 transmitters. Gerdes et al [12] used physical layer signal processing to distinguished between wired Ethernet NICs based on fragments of their signals.…”
Section: Radiometric Identificationmentioning
confidence: 99%
“…Perhaps the most intuitive and straightforward way of radiometric analysis was studied by Remley [29], who visually identified differences between signals of different 802.11 transmitters. Gerdes et al [12] used physical layer signal processing to distinguished between wired Ethernet NICs based on fragments of their signals.…”
Section: Radiometric Identificationmentioning
confidence: 99%
“…Further, recent studies show that target's wireless card can be identified by its unique physical layer properties, e.g. electromagnetic signature [18] or timing [19]. However, we consider the adversary does not employ such means that can involve significant effort for tracking even a single target vehicle, such as deploying expensive cameras with density sufficient for desired tracking resolution, or employing specialized hardware to capture and process electromagnetic signatures.…”
Section: A Trust Assumptions and Adversary Models Consideredmentioning
confidence: 99%
“…A natural augmentation is to constraint the estimation result by utilizing our nonlinearity model in (3). The estimated symbols are over-fitted to the model to reduce the error perpendicular to the solution plane and than they are re-projected back to the corresponding transmit symbols.…”
Section: Convergence Rate Improvementmentioning
confidence: 99%